Analisis Manajemen Risiko Pada UMKM “Bento Cake” Rancaekek - Sidik, Fajar; Meidinar Eka, Najwa (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This analysis discusses risk management in Micro, Small and Medium Enterprises as an important aspect of business sustainability. With increasingly competitive markets and increasing economic uncertainty, it is necessary to implement effective risk management strategies to minimize potential losses. This research identifies the types of risks commonly faced by Micro, Small and Medium Enterprises including financial, operational and market risks. Through Interview, and Observation. This research also explores the best practices in risk management that have been implemented. The purpose of this business research is for business people to understand risk management which is likely to happen and have an impact on the business they run. Results show that a good understanding of risk and implementation of appropriate mitigation strategies can improve resilience and performance. The results obtained for this "cabinet making" research are in order to develop policies that can improve risk management capabilities among Micro, Small and Medium Enterprises.